Why in Spain the Kidney Altruistic Donation Rate is Lower that of Other Countries of our Environment?. (July 2018) - Gracia, Marta; Valentin, Maria; Ormeño, Myriam; Martinez, Itziar; Dominguez-Gil, Beatriz
Abstract : Introduction: Spain has a national altruistic living kidney donation program since 2010. In this program the evaluation of each candidate is structured in three consecutive steps, which must be overcome to advance the process: 1. Initial semi-structured telephone interview from the ONT. 2. Evaluation in a hospital with a kidney transplant program. 3. Evaluation in a hospital with crossover kidney exchange program. The real effectiveness of the Spanish program is lower than that published by neighboring countries such as: UK, Netherlands and USA. Objective: Describe the characteristics of potential candidates for altruistic renal donation in Spain and the causes of dismissal at each level of evaluation. Know the characteristics of those candidates who finally managed to donate their kidney. Method: Retrospective, descriptive study of the epidemiological, motivational and pathological characteristics of all candidates for altruistic kidney donation in Spain, between January 2010 and December 2016. Resulted: 182 people showed interest in the altruistic donation, 67% of these (n = 123) was rejected after the initial interview conducted from the ONT, and the main reasons were: Medical contraindication (35%) and loss of interest after receiving specific information about the process (27%). The candidates who passed this first interview (n = 59), had an average age of 51.3 years, they were Spanish (88%), with secondary or higher education (65%, n = 40), active in work (62%, n = 47), without a current partner (62%, n = 45), with children (56%, n = 46) and 100% (n = 44) recognized an altruistic life course (39% were blood donors; 29% NGO volunteers, 22% bone marrow donors, 20% organ donors after death). The main motivation recognized was: "Awareness of the need for society" (32%) and "Improve the quality of life of other people" (23%). In the first hospital evaluation, 39% (n=23) were dismissed, mainly as a result of detected medical and/or psychiatric contraindications (78%). In the second hospital evaluation, 44% candidates were discarded (n=16), of which 65% were also due to medical and/or psychiatric contraindications. Finally, 13 of these candidates (7% total) satisfactorily surpassed the three levels of evaluation: 8 men and 5 women, with an average age of 49 years, with no medical history except overweight (2) and obesity (1). Conclusion: People, who present themselves as candidates for an altruistic kidney donation, have a history of helping others and a strong motivation towards donation. A significant number of candidates are rejected due to medical contraindications. It is necessary to perform an audit of medical contraindications to assess whether they are adequate.